Perspective of Faith According to Sheikh H. Mukhtar in the Book of Al-Sholah - Faizin, Faizin; Dafizki, Ashlih Muhammad; I, Martunus (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
Sheikh H. Mukhtar was a prominent Muslim scholar from Kerinci whose religious thought influenced Islamic communities in Kerinci, Malaysia, and the surrounding regions. As a leading figure in Islamic daʿwah, he played an important role in strengthening religious life, particularly in the domain of faith . This study employs qualitative research using a library research approach complemented by field research to examine the religious thought of Sheikh H. Mukhtar and its influence on contemporary religious practices in Kerinci. The research results show in theological matters, K.H. Mukhtar emphasized the purification of Islamic belief from superstition, bidʿah, and shirk, while firmly grounding faith in the teachings of the Qur’an and Sunnah. His understanding of iman, Islam, and tawḥid reflects the theological orientation of Ahl al-Sunnah wa al-Jamāʿah, with a clear tendency toward the Ashʿari tradition. Faith, according to K.H. Mukhtar, is not merely inner belief but must be affirmed verbally and manifested through righteous practice in accordance with divine guidance and the attributes of Allah. This perspective demonstrates his contribution to shaping a balanced and orthodox understanding of Islamic faith within the Kerinci Muslim community. Syekh H. Mukhtar adalah seorang ulama Muslim terkemuka dari Kerinci yang pemikiran keagamaannya memengaruhi komunitas Islam di Kerinci, Malaysia, dan wilayah sekitarnya. Sebagai tokoh terkemuka dalam dakwah Islam, beliau memainkan peran penting dalam memperkuat kehidupan keagamaan, khususnya dalam bidang iman. Studi ini menggunakan penelitian kualitatif dengan pendekatan penelitian kepustakaan yang dilengkapi dengan penelitian lapangan untuk mengkaji pemikiran keagamaan Syekh H. Mukhtar dan pengaruhnya terhadap praktik keagamaan kontemporer di Kerinci. Hasil Penelitian menunjukkan dalam hal teologi, K.H. Mukhtar menekankan pemurnian keyakinan Islam dari takhayul, bid'ah, dan syirik, sambil tetap berlandaskan pada ajaran Al-Qur'an dan Sunnah. Pemahamannya tentang iman, Islam, dan tauhid mencerminkan orientasi teologis Ahl al-Sunnah wa al-Jamāʿah, dengan kecenderungan yang jelas terhadap tradisi Asy'ari. Menurut K.H. Mukhtar, iman bukanlah sekadar keyakinan batin tetapi harus ditegaskan secara lisan dan diwujudkan melalui praktik yang benar sesuai dengan petunjuk ilahi dan sifat-sifat Allah. Perspektif ini menunjukkan kontribusinya dalam membentuk pemahaman yang seimbang dan ortodoks tentang iman Islam dalam komunitas Muslim Kerinci.